2015
DOI: 10.1039/c4ta05537c
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled three-dimensional hierarchical porous V2O5/graphene hybrid aerogels for supercapacitors with high energy density and long cycle life

Abstract: A self-assembled three-dimensional hierarchical porous V2O5/graphene hybrid aerogel for high-performance supercapacitor was synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(75 citation statements)
references
References 46 publications
0
74
0
1
Order By: Relevance
“…Generally, transition metal (Ru, Mn, Ni, Co, and V) oxides have been http://dx.doi.org/10.1016/j.colsurfa.2015.06.040 0927-7757/© 2015 Elsevier B.V. All rights reserved. employed as pseudocapacitor electrodes and have shown good pseudocapacitive performances [3][4][5][6][7][8][9]. Moreover, it has been found that the electrochemical performances of the electrode materials are strongly dependent on their sizes, morphologies and structures.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, transition metal (Ru, Mn, Ni, Co, and V) oxides have been http://dx.doi.org/10.1016/j.colsurfa.2015.06.040 0927-7757/© 2015 Elsevier B.V. All rights reserved. employed as pseudocapacitor electrodes and have shown good pseudocapacitive performances [3][4][5][6][7][8][9]. Moreover, it has been found that the electrochemical performances of the electrode materials are strongly dependent on their sizes, morphologies and structures.…”
Section: Introductionmentioning
confidence: 99%
“…(GN and MWCNT). 13,22,40 Since the specic capacitance is proportional to the area of CV curve, the largest curve area also indicates that WMNA possess larger specic capacitance than that of raw V 2 O 5 powder and V 2 O 5 aerogels. This may be a consequence of developed surface area, the synergistic effect and improved the electrical conductivity by GN and MWCNT.…”
Section: 38mentioning
confidence: 99%
“…22,25 The electrodes were prepared by homogeneous mixing active materials, acetylene black and poly(vinylidene uoride) (PVDF) dispersed in N-methylpyrrolidone (NMP) at the mass ratio of 8 : 1 : 1. The obtained mixture was coated onto graphite papers (1 cm  3 cm) and the area is about 1 cm 2 , and nally dried in a vacuum oven at 120 C for 12 hours.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…[10a,192] The specific capacitance and capacitance retention have been dramatically improved with the induce of rGO (Figure 16c). [193] Similarly, V 2 O 5 /rGO hybrid aerogels can be prepared following the procedures as shown in Figure 16d, where V 2 O 5 nanowires were grown on the rGO surface (Figure 16e). [193a] V 2 O 5 /rGO aerogel was measured to have a higher specific surface area and better capacitive performance than V 2 O 5 aerogel (Figure 16f).…”
Section: Vanadium Oxide Nanocomposites In Pseudocapacitorsmentioning
confidence: 99%